História e ficção: territórios em conflito em História do cerco de Lisboa, de José Saramago - Silva, Renata Alves da (2014)
Based on José Saramago s novel called História do cerco de Lisboa, this dissertation aims to feature and analyse the boundary or territoriality existent between History and Literature. The literary and poetic expression of the History seeks to examine carefully the analysis of the boundaries coursed by these two fields of knowledge Literature and History in the process of retrieving and writing about the human experience, whatever it may be in the past or in the present tenses. Our hypothesis is that the History will demonstrate the territoriality between the present and the past which are harmonized on the work, whose articulation to the contemporary culture does not behold the past as something definitely lost or whose rescue is anachronistic. The theoretical framework is based on the idea of the History to become the own novel theme, because it is inserted in the fiction as a part of its, generating dialogic and territoriality conflicts discourses between the present and the past tenses. Toward this, studious as Walter Benjamin, Giorgio Agamben, Mikhail Bakthin, Tzvetan Todorov, Paul Ricouer, Homi K Bhabba will be studied and recovered in their theoretical proposals to consolidate groundwork to the arguments of analysis and interpretation. The contemporary discussion about the boundaries between literature and history recovers in several manners foregoing controversies. One of them is the discussion about the value and the truth of the literary and historical narratives, whose relations interchange between opposition and complementary periods. In this sense, the analysis may assist to comprehend better the boundaries between both discourses and procedures with which they authenticate their truths and their values